Minimally Invasive Surgery for ICH Evacuation Combined With Deferoxamine Treatment Increased Perihematomal Claudin-5 and ZO-1 Expression Levels and Decreased BBB Permeability in Rabbits - Siying Ren; Shanshan Han; Likun Wang; Yuanxin Huang; Jing Wu; Guofeng Wu (Frontiers in Neurology, 2022)
ObjectiveTo investigate the role of minimally invasive surgery (MIS) in intracerebral hemorrhage (ICH) evacuation combined with deferoxamine (DFX) treatment on perihematomal tight junction protein (claudin-5 and ZO-1) expression levels and blood-brain barrier (BBB) permeability in rabbits.MethodsWe randomly assigned 65 male rabbits (weight: 1.9–2.6 kg) to a normal control group (NC group, 13 rabbits), hemorrhage model group (HM group, 13), DFX treatment group (DFX group, 13 rabbits), MIS group (MIS group, 13 rabbits), or MIS combined with DFX treatment group (MIS + DFX group, 13 rabbits). ICH was established in all of the groups except the NC group. MIS was performed to evacuate the hematoma 6 h after the ICH model was created in the MIS and MIS + DFX groups. The DFX and MIS + DFX groups were treated with DFX (100 mg/kg, dissolved in 2 mL of 0.9% saline solution, administered intramuscularly) at 2 h, and then every 12 h for 7 d. The same dose of 0.9% saline solution was administered to the NC, HM, and MIS groups at the same time points. Sixty-five rabbits were divided into 5 groups, and 13 rabbits in each group. Neurological deficit (i.e., Purdy's score) was recorded in all rabbits before euthanasia (N total = 65). In each group, 2 rabbits were used for iron concentration measurement (N total = 10), 2 rabbits were used for brain water content measurement (N total = 10), 3 rabbits were used for BBB permeability measurement (N total = 15), 3 rabbits were used for claudin-5, ZO-1 expression detection by Western Blotting (N total = 15), and 3 rabbits were used for claudin-5, ZO-1 mRNA detection by real-time PCR (N total = 15). On day 7, the rabbits were sacrificed and the perihematomal brain tissue was harvested to test the iron concentration, brain water content (BWC), tight junction proteins (claudin-5 and ZO-1) expression, and BBB permeability.ResultsPurdy's score, iron concentration, and BWC were lower in the MIS and MIS + DFX groups compared to the HM and DFX groups. The MIS + DFX group showed a significant decrease in these indicators. The use of MIS to evacuate the hematoma led to increased expression levels of claudin-5 and ZO-1, as well as decreased BBB permeability. The MIS + DFX group exhibited a remarkable increase in claudin-5 and ZO-1 expression levels and a significant decrease in BBB permeability.ConclusionsMIS combined with DFX treatment could increase the expression levels of perihematomal tight junction proteins (claudin-5 and ZO-1) expression, reduce BBB permeability, and improve the neurological function. MIS combined with DFX treatment may also prevent secondary brain damage following ICH.